International financial competitiveness and incentives to foreign direct investment - Axel Jochem (Deutsche Bundesbank, 2008)
In this paper an index of financial competitiveness is calculated that corresponds to the market-to-book ratio of inward FDI stocks. For a panel of five advanced economies from 1980 to 2006 it is shown that price competitiveness, stable inflation rates and registered patents have a positive impact on the index. Institutional factors like EMU membership or Anglo-Saxon legislation also play a role. Financial competitiveness in turn encourages FDI inflows whereas it benefits fixed investment relative to M&A. There is also some evidence that an innovative environment accelerates investment decisions by promoting competition among investors.
Keywords: F41; F23; F21; 330; Competitiveness; foreign direct investment; international integration; Finanzsektor; Standortwettbewerb; Index; Direktinvestition; Frankreich; Deutschland; Japan; Großbritannien; USA